Management Strategies for Creating Professional Learning Communities of Schools under The Bangkok Metropolitan Administration - Polanunt, Kaanwarin; Viseshsiri, Pongsin; Sumettikoon, Piyapong (Scholar: Human Sciences, 2016)
The objectives of this research were 1) to study the current and desirable state of the management for creating professional learning communities (PLCs) of schools under the Bangkok Metropolitan Administration (BMA) 2) to analyze strengths, weaknesses, opportunities and threats of the management for creating PLCs of schools under the BMA and 3) to develop management strategies for creating PLCs of schools under the BMA. The study was mixed method research. The samples were 209 schools under the BMA. The instruments used in this study were the questionnaire and the strategic evaluation form of feasibility and appropriateness. The data were analyzed by frequency, percentage, average, standard deviation, PNIModified and content analysis. The results showed the following: 1) the current state of the management to create the PLCs of schools under the BMA was overall at a high level ( = 4.10). When considering each attribute, shared leadership and shared decision-making were the highest average ( = 4.31). The desired state of the management to create the PLCs of schools under the BMA was at the highest level overall ( =4.69). When considering each attribute, shared leadership and shared decision-making were the highest average ( = 4.72). 2) The strengths were the shared leadership and shared decision-making and the shared vision, mission and goals; the weaknesses were collaboration and shared practice, the collective learning through inquiry, reflective dialogues and application of learning and the supportive conditions respectively. The technology was considered as the opportunity and the economic, the political and the social aspects were considered as the threats. 3) Five management strategies were developed including (i) To promote collaborative culture and shared practice; (ii) To promote collective learning and application of learning; (iii) To develop teachers’ capacities and to increase the effectiveness of the structural support; (iv) To raise the quality of shared vision, mission and goals; and (v) To increase the effectiveness of shared leadership and shared decision-making.